Family planning in inflammatory bowel disease: childlessness and disease-related concerns among female patients. Issue 3 (March 2018) - Walldorf, Jens; Brunne, Susanne; Gittinger, Fleur S.; Michl, Patrick
Abstract : Objective: Inflammatory bowel disease (IBD) frequently affects women when family planning and pregnancy (FPP) are important issues. This survey aimed to identify patients with an increased need for medical counselling. Patients and methods: An internet-based questionnaire was offered to women with IBD. Characteristics in terms of FPP were analysed with respect to sociodemographic and disease-related factors. Results: Childlessness was frequently reported (64.8% of 443 participants). In women older than 35 years with IBD, childlessness was significantly more prevalent than that in the general population (36.7 vs. 22.9%, odds ratio=1.9, P <0.001). Overall, 44.2% of the women were satisfied with counselling in general, and only 27.3% with the specific advice on FPP. Women younger than 25 years were rarely satisfied with the advice in terms of FPP (18.2%) and demanded an intensified counselling (44.6%). Frequent concerns were the heritability of IBD (all women, 59.2%; mothers, 51.5%; childless, 62.5%, P <0.01), medication during FPP (44.7, 26.1, 52.4%, P <0.01) and miscarriage (38.9, 16.8, 48.7%, P <0.01). Conclusion: The prevalence of childlessness in women with IBD compared with the general population increases with age. FPP-related worries, especially in terms of heredity, medication and miscarriage, are associated with an increased risk for childlessness. The results underline the importance of qualified counselling as early as possible during the course of the disase.